The Occurrence of Red-Back Spider Latrodectus hasselti (Araneae: Theridiidae) in Bandar Abbas, Southern Port of Iran - M Shahi; A Hosseini; K Shemshad; J Rafinejad (Tehran University of Medical Sciences, 2011)
Background:  Due to importance and fatal affect of Red-back spiders, Latrodectus hasselti, a faunistic survey for presence of this spider in Bandar Abbas has been conducted. This animal is considerably the most medically importance spiders all over the world. Methods: Live adult spider specimens were collected from Bandar Abbas town using hand catch conventional method and transferred to the laboratory throughout the summer of 2008. They  were identified based on morphological characteristics and taxonomic keys and confirmed by some external experts. Results: Results showed the occurrence of the red-back spider, L. hasselti from Bandar Abbas, southern port of Iran. Two female specimens were found. The spider had specific morphological characters  including black color with an obvious orange to red longitudinal strip on its upper parts of  abdomen. Conclusion: Although the specimens were collected from south of the country, however since the region is an important harbor and port and goods come form different parts of world we assume the possibility of arrival  from its origin and native breeding sites of the world. Therefore further investigation is needed to clarify the presence of this species in different parts of Iran.